Medication Monitoring and Optimization: A Targeted Pharmacist Program for Effective and Cost-Effective Improvement of Chronic Therapy Adherence - van Boven, Job F.M.; Stuurman-Bieze, Ada G.G.; Hiddink, Eric G.; Postma, Maarten J.; Vegter, Stefan (Journal of managed care & specialty pharmacy, 2014)
Community pharmacies provide a promising platform for monitoring and improving therapy adherence and providing pharmaceutical care. Structured methods and appropriate software are important tools to increase pharmacist effectiveness and improve health outcomes. In 2006, the Medication Monitoring and Optimization (MeMO) program was introduced in several community pharmacies in the Netherlands. MeMO facilitates targeted and continuous patient-centered pharmaceutical care around chronic medication, such as for osteoporosis, cardiovascular disease, and asthma/chronic obstructive pulmonary disease (COPD). To describe the MeMO program and summarize findings from publications on its effectiveness, patient satisfaction, and cost-effectiveness. In the first part of this article, the MeMO program is extensively described. In the second part, a review of the evidence of effectiveness, cost-effectiveness, and patient satisfaction of the MeMO program is provided. Evidence is based on 5 previously published articles. The MeMO program starts with structured counseling sessions with patients at the initiation and follow-up of chronic therapies. This process is followed by a continuous phase in which patients' therapy adherence is monitored on a monthly basis, using standardized search algorithms in the pharmacy database. When the algorithm detects a patient's discontinuation of therapy, tailored interventions are used to improve adherence and optimize pharmacotherapy. For osteoporosis patients, treatment discontinuation with bisphosphonates after 1 year dropped from 31.7% to 16.1% (P  less than  0.001). This program was shown to be cost-effective in patients initiating osteoporotic therapy. Future scenarios with lower drug prices (e.g., from generic prescribing) result in cost savings for the MeMO program. For lipid-lowering drugs, the MeMO program has been shown to lower therapy discontinuation after 1 year from 25.9% to 13.6% (P  less than  0.001). By extrapolating these results to patients' lifetimes, the intervention was estimated to be cost-effective, with gains for primary prevention of cardiovascular events, and even cost saving in secondary prevention. Results from the ongoing MeMO asthma/COPD program are promising, showing marked improvements in therapy control and quality of life for asthma and COPD patients. Almost all patients participating in MeMO programs are satisfied with the pharmacy team and have gained knowledge of the effectiveness and administration of their medications and the importance of therapy adherence. The MeMO program is an effective and structured method to improve patients' adherence to chronic medication in the field of osteoporosis, lipid-lowering drugs, and asthma/COPD and is well received by patients. By targeting the program toward nonadherent and high-risk patients, the program showed favorable cost-effectiveness.